Adherence to Definitions of Labor Arrest Influence on Primary Cesarean Delivery Rate - Greenberg, Jessica T.; Cross, Sarah N.; Raab, Cheryl A.; Pettker, Christian M.; Illuzzi, Jessica L. (American Journal of Perinatology, 2022)
Objective The cesarean delivery rate in the United States is 31.9%. One of the leading indications for primary cesarean delivery is labor arrest. A modern understanding of the labor curve supports more time prior to the diagnosis of labor arrest. We conducted this study to examine the impact of adherence to the modern criteria for labor arrest and failed induction on rates of primary cesarean delivery and to identify predictors of meeting these criteria.Study Design We analyzed rates of primary cesarean deliveries overall and primary cesarean deliveries occurring due to arrest of dilation, arrest of descent, and failed induction among the 17,877 live births at a large academic center from 2010 through 2013. Multiple logistic regression modeling identified predictors of meeting the new criteria for these indications based on guidelines published by the 2012 National Institute of Child Health and Human Development.Results The primary cesarean delivery rate decreased from 23.5 to 21.1% (p = 0.026) from 2010 to 2013. Primary cesarean delivery rate for labor arrest and failed induction decreased from 8.5 to 6.7% (p = 0.005). The percentage of primary cesarean deliveries meeting the 2012 criteria for labor arrest increased from 18.8 to 34.9% (p = 0.002), and the rate of primary cesarean deliveries due to arrest of dilation decreased from 5.1 to 3.4% (p < 0.0005). The percentage of cases meeting the 2012 criteria for arrest of descent increased from 57.8 to 71.0% (p < 0.007), while primary cesarean delivery rate due to arrest of descent remained relatively unchanged, 3.1 to 2.6% (p = 0.330).Conclusion A decrease in the primary cesarean rate was attributable to a decrease in cesarean for arrest of dilation in the setting of a significant increase in meeting the 2012 criteria for arrest of dilation. At the end of the study period, 65.2% of cesareans still did not meet the criteria for arrest of dilation. Greater rates of adherence to these guidelines may yield further reductions in the cesarean rate.Key Points
Keywords: arrest of descent; arrest of dilation; failed induction of labor; labor arrest; labor curve; primary cesarean delivery; indication for cesarean delivery